2019
DOI: 10.3390/agronomy9020046
|View full text |Cite
|
Sign up to set email alerts
|

Dried Pig Manure from a Cogeneration Plant as a Fertilizer for Nitrate Vulnerable Zones

Abstract: Nitrate vulnerable zones (NVZs) are areas considered to be at high risk of water pollution due to an excess of nitrates and, according to European regulations, codes of good agricultural practice are to be implemented by farmers, such as reducing doses of the applied fertilizers, or the use of fertilizers that minimize nitrate leaching. In this work, the influence of organic fertilization with dried pig manure (DPM) as compared to mineral fertilization with ammonium sulfate nitrate with 3,4-dimethylpyrazole ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In subtropical China, the threshold for long-term application of pig manure from an environmental safety perspective would be 3.6 t ha −1 [33]. However, in Valladolid, Spain, the highest yields were attained at an application rate of 9.5 t ha −1 for swine manure, much higher than the rate (6 t ha −1 ) used in the study [11]. Also, there were studies showing that pure manure application resulted in lower N availability in the early stages of crop development as it had a lower speed of nutrient release than mineral NPK did.…”
Section: Yields Boosting Effect Of Ridge and Furrow Planting With Manmentioning
confidence: 70%
See 2 more Smart Citations
“…In subtropical China, the threshold for long-term application of pig manure from an environmental safety perspective would be 3.6 t ha −1 [33]. However, in Valladolid, Spain, the highest yields were attained at an application rate of 9.5 t ha −1 for swine manure, much higher than the rate (6 t ha −1 ) used in the study [11]. Also, there were studies showing that pure manure application resulted in lower N availability in the early stages of crop development as it had a lower speed of nutrient release than mineral NPK did.…”
Section: Yields Boosting Effect Of Ridge and Furrow Planting With Manmentioning
confidence: 70%
“…This method is regarded as a feasible approach to keep the rate of grain gain with zero growth of chemical fertilizers consumption. Also, manure amendment has the potential to boost yields through improving soil structure, and enhancing the capacity of water retention [11]. For example, on a degraded tropical Alfisol in south western Nigeria, it was reported that pure poultry manure application at 5 t ha −1 significantly increased maize yield by 60% and soil organic matter by 45%, compared with the application of N fertilizers at 100 kg ha −1 [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral fertilization treatments would result in the highest values of N content (Maleki-Farahani et al 2011;Wilczewski 2014), which shows a positive correlation with the amounts of N applied by mineral fertilization (up to 140 kg ha −1 ) (Wilczewski 2014). Although organic fertilization treatments typically lead to lower values, because of the greater difficulty to supply an adequate amount according to the needs of the plant (Maleki-Farahani et al 2011;Sánchez-Báscones et al 2019), there are exceptions in which organic fertilization treatments have reached similar values to those attained with mineral fertilization (Agegnehu et al 2016), or even higher values (Moreno et al 1996) (see Table 6).…”
Section: Nitrogenmentioning
confidence: 99%
“…However, the use of organic waste as fertilizers in agricultural soils can immobilize the nitrate content due to their organic matter content (Sánchez-Báscones et al 2019), and may increase the Na content, thus increasing soil salinity (Li-Xian et al 2007) and negatively affecting crop yield.…”
Section: Introductionmentioning
confidence: 99%